2014
DOI: 10.1098/rstb.2013.0254
|View full text |Cite
|
Sign up to set email alerts
|

The macroevolutionary consequences of phenotypic integration: from development to deep time

Abstract: Phenotypic integration is a pervasive characteristic of organisms. Numerous analyses have demonstrated that patterns of phenotypic integration are conserved across large clades, but that significant variation also exists. For example, heterochronic shifts related to different mammalian reproductive strategies are reflected in postcranial skeletal integration and in coordination of bone ossification. Phenotypic integration and modularity have been hypothesized to shape morphological evolution, and we extended s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
397
3
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(427 citation statements)
references
References 127 publications
(225 reference statements)
24
397
3
3
Order By: Relevance
“…The trend for the face to elongate with allometry has also been noted in mammals (17) and is postulated to be related to heterochrony, an important factor in the evolution of birds from dinosaurs (46) and a demonstrated mode of generating diversity of beak forms in Darwin's finches (6,9). In mammals, it has been shown that integration constrains evolution along paths of least evolutionary resistance, meaning that heterochronic or allometric changes offer a simple mechanism by which evolution can act to produce high disparity (47,48). The fact that two nonsister clades of accipitrid vultures achieve a vulturine morphology solely by increasing skull size provides a new, nonmammalian example of this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…The trend for the face to elongate with allometry has also been noted in mammals (17) and is postulated to be related to heterochrony, an important factor in the evolution of birds from dinosaurs (46) and a demonstrated mode of generating diversity of beak forms in Darwin's finches (6,9). In mammals, it has been shown that integration constrains evolution along paths of least evolutionary resistance, meaning that heterochronic or allometric changes offer a simple mechanism by which evolution can act to produce high disparity (47,48). The fact that two nonsister clades of accipitrid vultures achieve a vulturine morphology solely by increasing skull size provides a new, nonmammalian example of this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Over time, the effect of phenotypic integration will produce taxa that are both more divergent and less divergent in morphology than would be otherwise expected (Fig. 2C) (63).…”
Section: Evolvability and Modularity: The Macroevolutionary Consequenmentioning
confidence: 99%
“…Analyses of morphological disparity and integration have compared trait variances in strongly and weakly integrated traits across a few clades of mammals, suggesting that strong integration may constrain trait variation across taxa although its effect is relatively weak (64). Interestingly, this weak effect on disparity may not translate simply to evolutionary rates because some of the most strongly integrated cranial traits showed limited disparity but high rates of evolution in an analysis across carnivorans (63). These results present one possible hypothesis: Phenotypic integration may constrain morphological variation to certain "preferred" directions but has little influence on the speed of changes within the allowed space, a pattern that reflects previous studies finding that evolution is more bounded by constraints than predicted (65).…”
Section: Evolvability and Modularity: The Macroevolutionary Consequenmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have argued that modularity facilitates evolutionary change [418][419][420][421], a hypothesis that has been investigated with the methods of geometric morphometrics [172,[422][423][424]. Also, some authors have hypothesized that the patterns of genetic and developmental modularity should evolve to match the patterns of functional modularity [399,419,[425][426][427].…”
Section: Morphometric Analyses Of Covariation Of Fluctuating Asymmetrymentioning
confidence: 99%